Urinary Tract Infection Etiological Profiles and Antibiotic Resistance Patterns Varied Among Different Age Categories: A Retrospective Study From a Tertiary General Hospital During a 12-Year Period - Huang, Lei; Huang, Chenwei; Yan, Yan; Sun, Liying; Li, Haixia (Frontiers in Microbiology, 2022)
Background: Urinary tract infections (UTIs) are among the most common infections worldwide. With continuing trends of antibiotic resistance, the etiological distribution and antibiotic susceptibility surveillance are of great importance for empirical antimicrobial therapy. The risk factors and clinical circumstances of UTI among different age categories varied, thus the pathogens and antimicrobial susceptibilities of UTI may also change with age. The aim of this study was to compare the etiological profiles and antibiotic resistance patterns of UTIs sorted by different age categories from a tertiary general hospital during a 12-year period. Methods: All positive urine culture results from non-repetitive UTI patients in our hospital from January 2009 to December 2020 were collected retrospectively. The microbial distribution and antibiotic resistance rates were analysed by WHONET 5.6 software. The etiological profiles sorted by different age categories (newborn, pediatric, adult, and geriatric) and antibiotic resistance rates of the top 5 pathogens were analysed. Results: A total of 13308 non-repetitive UTI patients were included in our study. Enterococcus faecium was dominant in newborn (45%, n=105), and replaced by Escherichia coli in pediatric (34%, n=362), adult (43%, n=3416) and geriatric (40%, n=1617), respectively. The etiological profiles of different age categories were divergent, sorted by genders (male and female) and ward types (outpatient, inpatient, ICU, and emergency). E. coli, Klebsiella pneumoniae, Enterococcus faecalis, E. faecium, and Pseudomonas aeruginosa were the top 5 pathogens in all age categories. The resistance rates of cefoperazone-sulbactam and piperacillin-tazobactam in E. coli were low in all age categories. The resistance rates of other cephalosporins, carbapenems, and fluoroqinolones in K. pneumoniae were higher in geriatric patients overall. E. faecium was more resistant than E. faecalis in all age categories. Multidrug resistance increased with age, which was more serious in geriatric patients. Conclusions: The UTI etiological profiles and antibiotic resistance patterns varied among different age categories, especially in pediatric and geriatric patients, thus different antibiotic therapy for various age categories should be considered when initiating empirical antimicrobial therapies.